Ultra-Widefield Fluorescein Angiography Findings in Patients with Macular Edema Following Cataract Surgery. (3rd April 2021) - Baek, Jiwon; Lee, Mee Yon; Kim, Boyun; Choi, Ayoung; Kim, Juhye; Kwon, Hyunggoo; Jeon, Sohee
ABSTRACT: Purpose : To evaluate the ultra-widefield fluorescein angiography (UWFA) findings in patients with macular edema (ME) following cataract surgery. Methods : Thirty-three eyes from patients who showed greater than a 30% increase in the central subfield thickness following cataract surgery were included. UWFA scored according to a system suggested by the Angiography Scoring for Uveitis Working Group (ASUWG). Factors associated with a high ASUWG score were evaluated. Results : Thirty-three (100.0%) of the 33 eyes showed abnormal UWFA findings, including optic disc staining (81.8%), capillary leakage (100.0%), pinpoint leakage (84.8%), peripheral retinal vascular leakage (24.2%) and retinal staining (6.1%). Multiple regression analysis reveals that following adjustment for other factors, younger age was independently associated with a higher ASUWG score (R 2 = 0.476, p = .001). Conclusions : Patients with ME following cataract surgery show generalized inner and outer blood−retinal barrier breakage. Particular attention is required during cataract surgery in young patients.